1997
DOI: 10.1128/jvi.71.11.8204-8212.1997
|View full text |Cite
|
Sign up to set email alerts
|

Collectin-mediated antiviral host defense of the lung: evidence from influenza virus infection of mice

Abstract: Collagenous lectins (collectins) present in mammalian serum and pulmonary fluids bind to influenza virus and display antiviral activity in vitro, but their role in vivo has yet to be determined. We have used early and late isolates of H3N2 subtype influenza viruses that differ in their degree of glycosylation to examine the relationship between sensitivity to murine serum and pulmonary lectins in vitro and the ability of a virus to replicate in the respiratory tract of mice. A marked inverse correlation was fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
143
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(154 citation statements)
references
References 53 publications
11
143
0
Order By: Relevance
“…Similarly, SP-A and SP-D can both interact with influenza to prevent the association of the HA with its receptor. Binding of MMR, MBL or SP-D to influenza A virus involves the carbohydrate recognition domain of the molecule and high-mannose oligosaccharides of the viral proteins hemagglutinin and neuraminidase [63][64][65][66] and can potentially lead to internalization of the lectin-virus complex and delivery of complexed virus to degradative compartments for processing and presentation by the immune system (Figure 2b). MMR and SP-D can additionally bind to HIV and prevent entry and replication [67].…”
Section: Impact Of Viral Glycosylation On Immune Factor Interactionmentioning
confidence: 99%
“…Similarly, SP-A and SP-D can both interact with influenza to prevent the association of the HA with its receptor. Binding of MMR, MBL or SP-D to influenza A virus involves the carbohydrate recognition domain of the molecule and high-mannose oligosaccharides of the viral proteins hemagglutinin and neuraminidase [63][64][65][66] and can potentially lead to internalization of the lectin-virus complex and delivery of complexed virus to degradative compartments for processing and presentation by the immune system (Figure 2b). MMR and SP-D can additionally bind to HIV and prevent entry and replication [67].…”
Section: Impact Of Viral Glycosylation On Immune Factor Interactionmentioning
confidence: 99%
“…Having bound to microbial pathogens, MBL mediates killing through lectin complement pathway activation and opsonophagocytosis. MBL has been observed to bind to and neutralize the influenza virus in studies involving nonpandemic H3N2 strains [3]. In this study, the efficacy of MBL-mediated inhibition of these influenza strains that have multiple exposed glycosylation sites on the hemagglutinin head was proportional to the number of glycosylation sites available for MBL binding.…”
Section: Introductionmentioning
confidence: 78%
“…The obvious conclusion is that MBL is not involved in innate immune responses to influenza or other respiratory viruses. This is countered, however, by the in vitro evidence of MBL's inhibition of influenza virus [3,18], recent evidence of MBL's role in the development of humoral immunity to influenza [19], and clinical association studies that demonstrate that MBL deficiency predisposes not only to respiratory tract infection in general, but also to respiratory tract infections with viral pathogens like severe acute respiratory syndrome in particular [7].…”
Section: Discussionmentioning
confidence: 99%
“…162,163,163a,163b It is interesting to note that the annual severity of influenza infections is related to the ability of SP-D to bind to the circulating strains of influenza. 163,164 Strains with less SP-D binding such as the 1918 H1N1 strain and the pandemic 2009 strain are clinically more virulent. Although studies on the interaction of SP-D with viruses have been reported for only a few viruses, it is likely that SP-D binds to many respiratory viruses.…”
Section: Secretion and Extracellular Processing Of Surfactantmentioning
confidence: 99%